PELATIHAN MEMBATIK DENGAN TEKNIK SHIBORI BAGI IBU PKK DESA SEBAMBAN BARU - Rina Dewi; Marlina Marlina; Tata Adestia Cahyani; Nurbaiti Janati; Mirnawati Mirnawati; Baiti Jannah (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2025)
Empowerment activities are very important in improving skills and economic independence. One form of empowerment is through batik training with the shibori technique which is a folding, tying and dyeing technique that will produce unique motifs. This shibori batik making training was carried out for PKK mothers in Sebamban Baru Village. This activity aims to train the skills of PKK mothers in Sebamban Baru Village in working and being productive. The method applied in this activity is a combination of theory and direct practice, including the provision of materials, accuracy. In this training, participants use tools and materials that are easy to find. Direct practice and Evaluation. This activity was held on February 12, 2025. The results of the implementation of this activity were the enthusiasm and enthusiasm of PKK mothers in learning how to make batik with various unique motifs using the shibori technique. In addition to being used for themselves, the results of shibori batik also have the potential to be sold, so that they can increase the value of the fabric and contribute to the welfare of the community.